Norm-determining subspaces - Sarembock, Sandra Jacqueline (Department of Mathematics and Applied Mathematics, 2015)
This thesis will centre on the concept of norming subspaces in the dual of a Banach space. We shall consider a weakly-dense subspace V of E', and the natural norm it generates on E. If this new norm is equivalent to the original norm on E, then V is called norming or norm-determining.